The 1919 and 1935 rice crises in the Philippines the rice market and starvation in American colonial times - Chiba, Yoshihiro (Philippine studies : historical and ethnographic viewpoints, 2010)
"This article analyzes starvation as a part of poverty in the Philippines under American control, particularly during the period of the 1920s to the 1930s. It looks into how the starvation was brought about by the rice crises that happened in 1919 and 1935. Rather than discussing poverty from standpoints such as the inequitable distribution of land and unemployment, this study focuses on the rice market as a space connecting various diversified phases such as trading, ownership of productive resources, labor, and policies as crucial to understanding starvation, while emphasizing merchants' activities. It argues that the trading environment caused the starvation of lower classes.